The educational effects of school start times - Teny Maghakian Shapiro (IZA World of Labor, 2015)
The combination of changing sleep patterns in adolescence and early school start times leaves secondary school classrooms filled with sleep-deprived students. Evidence is growing that having adolescents start school later in the morning improves grades and emotional well-being, and even reduces car accidents. Opponents cite costly adjustments to bussing schedules and decreased time after school for jobs, sports, or other activities as reasons to retain the status quo. While changing school start times is not a costless policy, it is one of the easiest to implement and least expensive ways of improving academic achievement.
Keywords: I20; 330; start times; biorhythms; sleep; secondary education; education production function